INTEGRATED PLANT NUTRIENT SUPPLY SYSTEM IN PREDOMINANT SUB-TEMPERATE MIDHILL CROPPING SYSTEMS OF JAMMU THROUGH - KUMAR, ANIL; THAKUR, N.P; BALI, AMARJIT S.; DIXIT, ANOOP; MEHTA, SUMAN (Annals of Agricultural Research, 2014)
A field experiment with two predominant cropping system, viz., rice (Oryza sativa)-wheat (Triticum aestivum L.) and maize (Zea mays)-wheat were carried out for three years (2001-02 to 2003-04) in participatory mode on farmer’s fields in Jammu. Treatments compr in-situ green manuring Dhaincha + 100 and 50% recommended NPK in rice -wheat cropping system whereas in maize-wheat cropping system instead of green manuring, farmer’s practice was taken as a treatment for comparison. The treatments Dhaincha (GM) + 100% NPK, No FYM + 100% NPK, FYM @ 5t/ha + 100% NPK, FYM @ 5t/ha + 50% NPK in rice-wheat cropping system gave 19.5, 14.5, 25.4 and 4.8% higher net returns over GM+50% NPK. In maize-wheat system, the treatments FYM @ 5 t/ha + 100% NPK, FYM @ 5 t/ha + 50% recommended NPK and no FYM + 100% NPK gave 31.5, 9.5 and 19.0% higher net returns over farmer’s practice, respetively. Use of FYM in combination with chemical fertilizers in rice-wheat and maize-wheat resulted in 50% saving of chemical fertilizers, as the produtivity was omparable with 100% chemical fertilizers alone. In-situ green manuring in rice compared well with FYM with respect to crop yields at same level of chemical fertilizers and recorded highest benefit-cost ratio. Integratd plant nutrient supply (IPNS) system in rice-wheat and maize-wheat cropping system improved soil fertility after 3 crop cycles.